Indonesia Student Fitness: A Quantittive Descriptive Study SDN 5 Sungai Ulin, Banjarbaru - Ridha, Sahbana; Mashud, Mashud; Warni, Herita; Arifin, Syamsul (Lambung Mangkurat University, 2024)
This study aims to describe the physical fitness levels of students at SDN 5 Sungai Ulin based on the results of the TKSI Stage B test, evaluated by individual test items. A descriptive quantitative approach was used in this research. The study was conducted at the elementary school field of SDN 5 Sungai Ulin, Banjarbaru. The subjects were third and fourth-grade students, consisting of 104 students (52 males and 52 females) aged 8-10 years during the 2024/2025 academic year. The survey method was employed, with data collected through the Indonesian Student Fitness Test (TKSI). The Stage B TKSI results include five main assessment items: V Sit and Reach Test, Half Up Test, Hand-Eye Coordination Test, T-test, and Around the World Test. These five fitness tests provide a comprehensive picture of various physical fitness aspects, including flexibility, abdominal strength, hand-eye coordination, agility, and cardiovascular endurance. In general, most students fall within the